Hardware‐in‐the‐loop testing of impedance protection with compensation of fault impedance and DG infeed current. Issue 15 (20th August 2018) - Pandakov, Konstantin; Adrah, Charles Mawutor; Liu, Zou; Høidalen, Hans Kristian; Kure, Øivind
Abstract : The standard impedance protection deployed in distribution networks can malfunction due to underreach errors caused by fault impedances and remote infeed currents from embedded generators (becoming more and more widespread). This paper introduces a compensation method aiming at elimination of these issues and enhancement of relay dependability. As an advantageous outcome, compensated measurements can be utilised for accurate fault location. The method is verified on ABB RED 670 relay in the loop with an OPAL‐RT real‐time simulator. As the method is based on multi‐point measurements, the test setup also contains a communication network emulator for modelling network delays and imperfections. The laboratory tests verify applicability of the method with proper appearance of the tripping signals from the relay. The fault location results based on synchronised data show overreaching inaccuracy rising with fault resistance. Though communication network delays and imperfection of the channels lead to underreaching, it has been revealed that not strict requirements for data synchronisation can be applied to specific measurements.